The effect of docosahexaenoic acid (DHA) supplementation on total antioxidant capacity (TAC), superoxide dismutase (SOD), and interleukin-6 levels in underweight pregnant women - Salmon Charles Siahaan; Budi Santoso; Kanti Ismayani; Natalia Yuwono; Mohd Aznan Md Aris (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS